Giant meat-eating dinosaurs - West, David, 1956- (New York : Windmill Books, 2016)
Describes the physical characteristics and behavior of meat-eating dinosaurs, including Allosaurus, Majungasaurus, and Suchomimus.
Keywords: Dinosaurs -- Juvenile literature; Predatory animals -- Juvenile literature; Carnivorous animals, Fossil -- Juvenile literature; Dinosaurs; Predatory animals; Carnivorous animals, Fossil; Dinosaurs; Predatory animals; Fossil reptiles